The role of game (wild boar and roe deer) in the spread of tick-borne encephalitis in the Czech Republic - Kriz, Bohumir; Daniel, Milan; Benes, Cestmir; Maly, Marek (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2014)
In the Czech Republic, the incidence of human tick-borne encephalitis (TBE) has been increasing over the last two decades. At the same time, populations of game have also shown an upward trend. In this country, the ungulate game is the main host group of hosts for Ixodes ricinus female ticks. This study examined the potential contribution of two most widespread game species (roe deer [Capreolus capreolus] and wild boar [Sus scrofa]) to the high incidence of TBE in the Czech Republic, using the annual numbers of culls as a proxy for the game population. This was an ecological study, with annual figures for geographical areas-municipalities with extended competence (MEC)-used as units of analysis. Between 2003 and 2011, a total of 6213 TBE cases were reported, and 1062,308 roe deer and 989,222 wild boars were culled; the culls of roe deer did not demonstrate a clear temporal trend, but wild boar culls almost doubled (from 77,269 to 143,378 per year). Statistical analyses revealed a positive association between TBE incidence rate and the relative number of culled wild boars. In multivariate analyses, a change in the numbers of culled wild boars between the 25th and 75th percentile was associated with TBE incidence rate ratio of 1.23 (95% confidence interval 1.07-1.41, p=0.003). By contrast, the association of TBE with culled roe deer was not statistically significant (p=0.481). The results suggest that the size of the wild boar population may have contributed to the current high levels and the rising trend in incidence of TBE, whereas the regulated population of roe deer does not seem to be implicated in recent geographical or temporal variations in TBE in the Czech Republic.
Keywords: viry klíšťové encefalitidy; Tick-borne encephalitis; Arachnid Vectors; Animals, Wild; Statistics, Nonparametric; Ixodes; Incidence; Česká republika; Encephalitis, Tick-Borne; Tick Infestations; incidence; vysoká zvěř; Wild boar; neparametrická statistika; Sus scrofa; Czech Republic; Encephalitis Viruses, Tick-Borne; Swine Diseases; infestace klíšťaty; klíšťová encefalitida; nemoci prasat; Swine; divoká zvířata; Game; ženské pohlaví; zvířata; Humans; zeměpis; Deer; arachnida jako vektory; prasata; klíště; Geography; Female; lidé; Roe deer; Animals